Measurement of Dynamic On-State Resistance of High-Voltage GaN-HEMTs under Real Application Conditions - Kohlhepp, Benedikt; Kuring, Carsten; Peller, Stefan; Kübrich, Daniel (22nd European Conference on Power Electronics and Applications (EPE'20 ECCE Europe), 2020)
GaN-HEMTs gain a lot of attention to power electronics engineers. However, they could exhibit increased on-state resistance due to charge trapping. This paper focusses on measuring this effect for high voltage devices. Measurements reveal an unexpected blocking voltage dependency of on-state resistance. Therefore, a second measurement setup serves as verificatio

Test Setup for Loss Measurements of Inductive Components by using GaN-HEMTs - Kohlhepp, Benedikt; Peller, Stefan; Kübrich, Daniel; Dürbaum, Thomas (2020 IEEE 21st Workshop on Control and Modeling for Power Electronics, COMPEL 2020, 2020)
This paper describes and verifies a measurement setup based on GaN semiconductors to characterize losses of inductive components used in switched-mode power supplies. Due to insufficient datasheet parameters, especially core losses occurring in inductive components cannot be accurately calculated by simulation. Furthermore, proximity losses within windings are difficult to obtain due to inhomogeneous field distributions within inductive components. Therefore, the ability to measure losses of inductive components plays an important role in the development of power supplies. Conventional test setups use the DUT's AC voltage and current to obtain the losses. Based on [1] this paper designs and verifies a circuit that allows for loss measurements of inductive components by only employing DC voltage measurements. After a presentation of the measuring principle and the resulting test setup realization, it is verified by measuring the well-defined losses of an air coil.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Core loss; Half-bridge; Power measurement; Rectangular voltage

Test setup using DC metering approach for loss measurements of inductive components – principle, characterization, validation and application - Kohlhepp, Benedikt; Kübrich, Daniel; Peller, Stefan; Dürbaum, Thomas (Iet Power Electronics, 2021)
Accurate loss estimation of magnetic components is crucial for power electronics engineers. Unfortunately, loss predictions remain a quite challenging task, as these depend on many parameters and manufacturers typically do not deliver a sufficient database for precise loss estimations. Therefore, this paper revisits an approach allowing loss measurements. In contrast to the most common used approach using alternating current (AC) waveforms to gain information about the losses, this approach relies on measuring direct current (DC) voltage and current. After characterizing the experimental setup, air inductors serve as references to validate the approach. In a first step, the test setup is used to extract core losses with and without DC bias by designing a special device under test (DUT) featuring low winding loss. Furthermore, this paper demonstrates that the test setup is also able to gain the overall losses of complete magnetic components by using the DC metering approach.
CRIS-Team Scopus Importer:2021-06-18